Management Of Character Education Of Islamic Boarding Schools in Improving the Independence Of Students (Qualitative Descriptive Study at Miftahul Muta'alimin Islamic Boarding School and Tahsinul Akhlaq Islamic Boarding School in Cirebon Regency) - Syarif Abubakar; Sutaryat Trisnamansyah; Hanafiah; Faiz Karim Fatkhullah (IJGIE (International Journal of Graduate of Islamic Education), 2022)
The low independence of Islamic boarding school graduates in the field of skills is still visible today, because the planning, implementation and supervision of Islamic boarding school character education has not been maximized in increasing the independence of students. The purpose of this study is to obtain an overview of planning, implementation, monitoring, inhibiting factors, and efforts to overcome obstacles. This study uses a descriptive method with a qualitative approach through observation, interviews, and documentation studies. The results showed that: : 1) Planning has been carried out according to the theory through curriculum and programs according to the pesantren model, but has not been supported by policies on developing skills programs and infrastructure resources. 2) The implementation has been carried out according to the theory through socialization, coordination and motivation, but it has not been maximal in shaping the character of the independence of students because of the lack of support for HR competencies. 3) Supervision has been carried out according to the theory through direct observation and assessment, but has not been maximized because it is still focused on the core program. 4) Inhibiting factors include the lack of core program learning facilities and skilled professionals. 5) Efforts to overcome obstacles through approaches, sanctions, expand alumni collaboration, and fundraising. Management of character education in increasing the independence of students in Islamic boarding schools in Cirebon Regency has been carried out according to management theory through the stages of planning, organizing, implementing, and supervising according to the curriculum and programs developed, but has not been maximized in forming students' independence due to policy and resource constraints